Quickbooks pro 6.0 for accounting - Owen, Glenn (South Western College Pub., 2000)
USING QUICKBOOKS FOR ACCOUNTING 6.O teaches you to use today's #1 best selling software from Intuit. With this books unique step by step method you will be able apply basic accounting principles to QuickBooks 6.0